Aerobic steps as measured by pedometry and their relation to central obesity - Duchečková, Petra; Forejt, Martin (Iranian journal of public health, 2014)
BACKGROUND: The purpose of this study was to examine the relation between daily steps and aerobic steps, and anthropometric variables, using the waist-to-hip ratio (WHR) and waist-to-height ratio (WHtR). METHODS: The participants in this cross-sectional study were taken the measurements of by a trained anthropologist and then instructed to wear an Omron pedometer for seven consecutive days. A series of statistical tests (Mann-Whitney U test, Kruskal-Wallis ANOVA, multiple comparisons of z' values and contingency tables) was performed in order to assess the relation between daily steps and aerobic steps, and anthropometric variables. RESULTS: A total of 507 individuals (380 females and 127 males) participated in the study. The average daily number of steps and aerobic steps was significantly lower in the individuals with risky WHR and WHtR as compared to the individuals with normal WHR (P=0.005) and WHtR (P=0.000). A comparison of age and anthropometric variables across aerobic steps activity categories was statistically significant for all the studied parameters. According to the contingency tables for normal steps, there is a 5.75x higher risk in the low-activity category of having WHtR>0.50 as compared to the high-activity category. CONCLUSIONS: Both normal and aerobic steps are significantly associated with central obesity and other body composition variables. This result is important for older people, who are more likely to perform low-intensity activities rather than moderate- or high-intensity activities. Our results also indicate that risk of having WHtR>0.50 can be reduced by almost 6x by increasing daily steps over 8985 steps per day.
Keywords: Physical activity; WHtR; WHR; Omron; Pedometer